The Position of a Marriage Agreement in Providing Legal Protection Against the Impact of Infidelity - Jannati, Shafiya Zilfa; Ginting, Lilawati (Universitas Islam Negeri Alauddin Makassar, 2026)
This study aims to analyze the position and function of prenuptial agreements in the Indonesian marital law system and their role in providing legal protection to parties harmed by infidelity. Infidelity is one of the main causes of marital breakdown that not only generates moral and psychological consequences but also produces legal and economic implications, particularly regarding the division of joint property and the fulfillment of post-divorce rights. This research employs a normative legal method using statutory and conceptual approaches supported by primary, secondary, and tertiary legal materials obtained through literature review. The findings show that prenuptial agreements function as a special legal instrument (lex specialis) that allows spouses to regulate deviations from the joint property regime as long as such arrangements do not contradict statutory law, religious values, and public morality. The legal development following Constitutional Court Decision Number 69/PUU-XIII/2015 expands the timeframe for making marriage agreements so that they may be concluded before or during the marriage. This development strengthens the function of prenuptial agreements as a preventive and repressive mechanism of legal protection against potential marital disputes, including those caused by infidelity. However, the scope of such agreements is legally limited because private parties cannot stipulate criminal sanctions for adultery, as criminal liability may only be determined by statutory law. Nevertheless, prenuptial agreements may regulate various civil consequences, including provisions concerning the division of property, maintenance obligations, compensation, and the protection of the rights of wives and children in the event of divorce due to infidelity. Therefore, a marriage agreement serves not only as an instrument for managing marital assets but also as a legal protection mechanism that anticipates the civil consequences of infidelity within the Indonesian marital law framework.